2005
DOI: 10.1007/s11252-005-1420-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-native plants in the understory of riparian forests across a land use gradient in the Southeast

Abstract: As urbanization expands into rural areas, an increase in the number of non-native plant species at the urban-rural interface is expected due in large part to the increased availability of propagules from ornamental plantings. A study investigating the distribution of non-native plants in the understories of riparian forests across an urban-to-rural gradient north of Columbus, GA was initiated in 2003. A significantly greater number of non-native plant species occurred at the urban sites and at one site at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 12 publications
6
45
0
Order By: Relevance
“…Although invasion rates have been shown to increase along urban-to-rural gradients (Loewenstein & Loewenstein 2005), little work has been done in marine habitats. Thus, we tested the hypothesis that the incidence of occurrence and abundance of Caulerpa racemosa increases with increasing levels of human disturbance, in the NW Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…Although invasion rates have been shown to increase along urban-to-rural gradients (Loewenstein & Loewenstein 2005), little work has been done in marine habitats. Thus, we tested the hypothesis that the incidence of occurrence and abundance of Caulerpa racemosa increases with increasing levels of human disturbance, in the NW Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…3-13). This decreasing pattern of plant species richness with increasing exotic cover was also shown by Loewenstein and Loewenstein (2005), where understory plant species richness (saplings, shrubs, herbs, vines) decreased with increasing cover of the exotic shrub Ligustrum sinense in riparian forests near Columbus, Georgia, USA. In the Louisville sites, Shannon's equitability index was negatively but weakly correlated with E. fortunei percent cover (Fig.…”
Section: Groundcover Plant Associations With Shrub Honeysucklesupporting
confidence: 61%
“…There are three predictions associated with this objective, the first being that groundcover plant diversity along this gradient would be higher in suburban riparian areas than in either urban or rural riparian areas for two reasons: 1) because of the likely greater availability of diverse seed from residential areas than in rural locations (McKinney 2008), and 2) because of the prevalence in urban riparian areas of Lonicera maackii, an invasive shrub known to reduce herb layer diversity (Collier et al 2002, Loewenstein andLoewenstein 2005) (see Chapter 2). The second prediction was that species richness would increase with total upstream catchment area, since other studies have shown that plant species richness increases with downstream distance (Bendix 1997, Bendix and Hupp 2000, Lite et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Urban forests are ideal systems to study the consequences of multiple exotic species introductions in forest ecosystems. Preventing invasions in urban forests is necessary to preserve the native diversity of major biomes since human centers embedded in natural areas are highly prone to exotic species invasions (Guirado et al 2006;Loewenstein and Loewenstein 2005;McKinney 2006;Vilà and Ibáñez 2011) and act as a potential invasion pathway to natural ecosystems.…”
Section: Insights and Perspectivesmentioning
confidence: 99%